The Void in Local Governance for Rural Development: Understanding Public Leadership in Village Transformation in Indonesia - Raharja, Wildan Taufik; Nurany, Fierda; Subagio, Dyajeng Puteri Woro; Bustami, Mohammad Reevany (Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to analyze the public leadership of a village head in development. This study posits that this discrepancy is mainly due to the difference in leadership competence in the various regions. Sekapuk Village, Ujungpangkah Sub-district, Gresik Regency, East Java Province, succeeded in achieving first place in Brilian Village in 2020. This accomplishment is inseparable from the visionary leadership role of the Sekapuk Village Head in managing village governance. The practical significance and the lessons of the findings of this study can be a reference for the public leadership of the village heads in the administration of other villages’s governance. This study analyzes the public leadership competence in development by utilizing the principles of good local governance for regional development. The methodology of this study involves a qualitative approach with a case study strategy. The researchers interviewed nine informants, consisting of village officials and heads as well as the community. The key research findings underline the ways in which public leaders are able to communicate constructively even with the opposition within the village governance structure and end up with the advancement of development in the region. The study, therefore, concludes that transformative public leadership is recommended for regional village development.